2009
DOI: 10.1016/j.socscimed.2009.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child dietary intake resemblance in the United States: Evidence from a large representative survey

Abstract: We studied the association in dietary intakes and patterns between parents (aged 20-65 years) and their children (aged 2-18 years), using nationally representative data collected by the US Department of Agriculture (USDA) in the Continuing Survey of Food Intake by Individuals 1994-96. We analyzed two 24-h recall dietary data for 1061 fathers, 1230 mothers, 1370 sons and 1322 daughters. All analyses adjusted for sampling design complexity. We assessed multivariate-adjusted parentchild correlations in selected n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
144
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(158 citation statements)
references
References 42 publications
11
144
3
Order By: Relevance
“…Parent child similarities exist for both healthy and unhealthy foods, including fat, soft drinks, snacks, milk, fruits and vegetables (Fisher et al 2004;Hanson et al 2005;Raynor et al 2011;Watts et al 2014). Ethnic differences have been little examined, but IG dietary influence appears highest among Hispanics (Beydoun and Wang 2009), with food availability data showing low income Hispanic children having greater access to fruits and vegetables than low income African American children (Skala et al 2012). Such IG influences are key, as learned preferences for fruits or vegetables can protect against obesity (Savage et al 2007).…”
Section: Intergenerational Transfermentioning
confidence: 99%
“…Parent child similarities exist for both healthy and unhealthy foods, including fat, soft drinks, snacks, milk, fruits and vegetables (Fisher et al 2004;Hanson et al 2005;Raynor et al 2011;Watts et al 2014). Ethnic differences have been little examined, but IG dietary influence appears highest among Hispanics (Beydoun and Wang 2009), with food availability data showing low income Hispanic children having greater access to fruits and vegetables than low income African American children (Skala et al 2012). Such IG influences are key, as learned preferences for fruits or vegetables can protect against obesity (Savage et al 2007).…”
Section: Intergenerational Transfermentioning
confidence: 99%
“…parents cutting up fruits or vegetables as a snack). Previous studies have found positive correlations between parents' fruit and vegetable intakes, parental modelling and those of their children (10,13,(17)(18)(19)(20)(21) . However, the fact that previous studies have used different methods to assess parents' and/or children's intake has complicated interpretations of the results.…”
mentioning
confidence: 93%
“…Previous studies have focused on parents as agents for healthy eating and physical activity in preschoolers (Beydoun and Wang, 2009;Zecevic et al, 2010). However, childcare centers have been identified as potential key locations for the promotion of healthy eating behaviors and physical activity as approximately 80% of preschoolers (2 to 5 years old) living in developed countries receive out-of-home care (Organisation for Economic Co-operation and Development, 2013), and spend a considerable amount of their waking hours in childcare centers.…”
Section: Introductionmentioning
confidence: 99%